Konsep Waktu: Perspektif Komunikasi, Islam, dan Anak TK - Rini Rinawati (MediaTor (Jurnal Komunikasi), 2007)
As pointed out by Dedy Mulyana, a scholar of communication science in Indonesia, communication act is definitely time-bounded. It was expressed in terms su:ch as “wasting time”, “saving time”, or verbatim such as “time is money”, “al-Waktu ka al-syaif”, etc. To explain more about time, Edward T. Hall uses Mandala model which describe time in terms of: biological time, personal time, physical time, metaphysical time, micro time, sync time, sacred time, profane time, and meta-time. There are two concepts of time, e.g. monochromic time and polychromic time. As consequences, communication message must be time-sensitive and designed specifically for communication receiver. This article explores time concept of children, and Islamic concept for Islam, which is uniquely defined and different with other time-concept.